The Effect of Beam Direction on Absorption and Transmission of Ultraviolet to Infrared Wavelength Regions in Three Different Dentin Thicknesses: The Effect (s) of Beam Direction on the loss of Light in Dentin - Eslami, Elmira; Kazeminejad, Ezatolah; Karimian, Azizeh; Khandan Fadafan, Hasan (Journal of Lasers in Medical Sciences, 2022)
Background: Lasers and optics have been used extensively in dental procedures in recent years, making the realization of the optical properties of the tooth a milestone in its successful applications. The aim of this study was to compare the absorption and transmission of applied wavelengths in the range of 190–1100 nm at different dentin thicknesses and the effect of changing the direction of radiation emission in the dentin tubules. Methods: Fifteen dentin specimens of thicknesses of 300, 600, and 1000 μm and five specimens of each thickness were prepared through a transverse section of the coronal dentin over the pulpal roof area of ​​human molars. Considering the coronal-apical and apical-coronal directions, we measured the absorption and transmission of parallel light rays perpendicular to the dentin samples in different thicknesses and two directions with a UV/Vis spectrometer. Results: The absorption rate of the ultraviolet wavelength was significantly higher than that of visible and infrared light irradiation from both directions at three thicknesses (p<0.001). Radiation shift direction had no significant differences in the absorption and transmission wavelengths of ultraviolet, visible, and infrared light in any of the three thicknesses (p >0.05). Conclusion: Accordingly, a change in beam direction does not cause a significant difference in light absorption.